Pillar depicting purnaghata kalasha - Temples of India Project Team (Jio Institute, 2024)
Details of the pillar (from inside the temple) flanking the staircase leading to the temple. The pillars depict purnaghata kalasha which is an auspicious motif and is mostly shown in temples regardless of regional stylistic variations. Above this kalasha, a manibandha is carved topped by a kirtimukha and the apex is carved with a triangular leaf motif.